2018
DOI: 10.1007/s00122-018-3110-x
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and epistatic interaction analysis of field resistance to sudden death syndrome (Fusarium virguliforme) in soybean

Abstract: Two interactive quantitative trait loci (QTLs) controlled the field resistance to sudden death syndrome (SDS) in soybean. The interaction between them was confirmed. Sudden death syndrome (SDS), caused by Fusarium virguliforme, is a major disease of soybean [Glycine max (L.) Merr.] in the United States. Breeding for soybean resistance to SDS is the most cost-effective method to manage the disease. The objective of this study was to identify and characterize quantitative trait loci (QTLs) underlying field resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…This resistance to SDS foliar chlorosis was also observed in a soybean variety GD2422 (Fig. 1B), which was a parent used in generating a recombinant inbred line (RIL) population with another parent,LD01-5907, which displayed susceptibility to SDS foliar chlorosis (Tan et al, 2018). These soybean RILs therefore became useful materials to test our hypothesis that SDS foliar chlorosis is controlled by a soybean S locus.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…This resistance to SDS foliar chlorosis was also observed in a soybean variety GD2422 (Fig. 1B), which was a parent used in generating a recombinant inbred line (RIL) population with another parent,LD01-5907, which displayed susceptibility to SDS foliar chlorosis (Tan et al, 2018). These soybean RILs therefore became useful materials to test our hypothesis that SDS foliar chlorosis is controlled by a soybean S locus.…”
mentioning
confidence: 63%
“…In our study, soybean varieties carrying STAY-GREEN alleles with a loss-of-susceptibility mechanism (d1d1d2d2 genotype) exhibited interveinal necrosis, and the leaves became dehydrated and fragile in response to the phytotoxin treatment. Moreover, the parent GD2422 (d1d1d2d2 genotype) was more susceptible in SDS field trials than another parent, LD01-5907 (Tan et al, 2018), and phytotoxins decreased photosynthesis efficiency in GD2422 faster than in LD01-5907 ( Fig. 3B).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Other evidence of SDS and SCN pleiotropy includes studies by Tan et al. (2018). This study mapped SDS resistance and found an epistatic resistance mechanism in regions overlapping with the rhg1 and Rhg4 alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Epistasis, interaction between one pair of loci located in the same or different chromosomes, as an important genetic basis of complex traits [18]. Some studies had shown that epistasis signi cantly affected the expression of genes and genetic variation underlying soybean [17,[19][20][21][22][23][24]. Hou et al(2014) [20] mapped oil content QTLs using simple repeat sequence (SSR) markers derived from Charleston and Dongnong594, which detected 4 pairs oil epistatic effect QTLs, and Qi et al (2017) [12] identi ed epistatic interactions for seed oil content under multi-environments based on a high-density single-nucleotide polymorphisms (SNP) using the same population.…”
Section: Introductionmentioning
confidence: 99%